Differences in the arrangement of the Pdr5p multidrug transporter binding pocket of Saccharomyces cerevisiae and Kluyveromyces lactis - Jancíková, Iva; Zahumenský, Jakub; Gbelská, Yvetta; Gášková, Dana (FEMS yeast research, 2017)
Multidrug transporters are often responsible for failure of medical treatment, since they expel a variety of structurally and functionally unrelated drugs out of the cell. We found that the fluorescent probe diS-C3(3) is a substrate of not only Pdr5p of Saccharomyces cerevisiae (ScPdr5p) but also of its less-explored Kluyveromyces lactis homologue (KlPdr5p). This enabled us to compare the ability of azoles to competitively inhibit the Pdr5p-mediated probe efflux in the two species. In K. lactis, these azoles completely inhibit probe transport by KlPdr5p and also compete with each other for transport. This indicates that the probe and the azoles are bound by the same site(s) of the KlPdr5p binding pocket. On the other hand, the azoles' capacity to inhibit the probe transport by ScPdr5p is limited, as a result of their partial cotransport with the probe. While the azoles bind to only one or two separate binding sites, the probe is able to bind to all three of them. Moreover, the bulky ScPdr5p substrate enniatin B, which effectively inhibits both probe and azole transport by the pump, has negligible effect on KlPdr5p. Our data point to a tighter arrangement of the KlPdr5p binding pocket compared to that of ScPdr5p.
Keywords: ATP-Binding Cassette Transporters; biologický transport; Azoles; Fluorescent Dyes; Saccharomyces cerevisiae Proteins; vazebná místa; Substrate Specificity; Saccharomyces cerevisiae; vazba proteinů; Binding, Competitive; ABC transportéry; fluorescenční protilátková technika; Fluorescent Antibody Technique; fluorescenční barviva; Biological Transport; Kluyveromyces; kompetitivní vazba; azoly; substrátová specifita; Saccharomyces cerevisiae - proteiny; Protein Binding; Binding Sites